Wali Nikah Sebagai Rukun Perkawinan dalam Hukum Islam: Analisis Normatif-Komparatif Mazhab Fikih dan Rekonstruksinya dalam Hukum Keluarga Islam Indonesia - Mustafa Parinduri; Muhammad Amar Adly (Yayasan Dar Arrisyah Indonesia, 2025)
Marriage in Islamic law is a legal contract that carries theological, social, and juridical consequences, the validity of which depends on the fulfillment of its essential pillars (arkān al-nikāḥ). Among these pillars, marriage guardianship (wali nikah) remains one of the most fundamental and contested issues in Islamic jurisprudence. This article examines the legal status of wali nikah as a pillar of marriage through a normative–comparative analysis of major Sunni legal schools and explores its reconstruction within Indonesian Islamic family law. Employing doctrinal legal research with a conceptual and comparative madhhab approach, this study analyzes classical fiqh texts alongside contemporary legal instruments, particularly the Indonesian Compilation of Islamic Law. The findings demonstrate that the majority of jurists (jumhūr) regard guardianship as a constitutive element determining the validity of marriage, primarily to ensure legal certainty and the protection of women’s interests. In contrast, the Hanafi school grants greater legal autonomy to adult women under specific conditions. The article argues that Indonesia’s adoption of the jumhūr position represents not merely a transplantation of classical doctrine but a normative reconstruction aimed at safeguarding legal order, women’s rights, and social stability within a modern Muslim legal framework.